The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1073/pnas.0711621105
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of P450 oxidoreductase: Sequence variation in 842 individuals of four ethnicities and activities of 15 missense mutations

Abstract: P450 oxidoreductase (POR) is an electron-donating flavoprotein required for the activity of all microsomal cytochrome P450 enzymes. We sequenced 5,655 bp of the POR gene in a representative population of 842 healthy unrelated individuals in four ethnic groups: 218 African Americans, 260 Caucasian Americans, 179 Chinese Americans, and 185 Mexican Americans. One hundred forty SNPs were detected, of which 43 were found in >1% of alleles. Twelve SNPs were in the POR promoter region. Fifteen of 32 exonic variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
176
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(198 citation statements)
references
References 39 publications
(61 reference statements)
9
176
3
6
Order By: Relevance
“…Our long-standing biochemical research into the mechanism of this critical flavoprotein (12) led us to explore the structure/ function relationships responsible for these phenotypes by expressing and purifying POR variants of interest reported in the literature (13)(14)(15)(16)(17)(18)(19)(20). The variant A287P was reported as the most common mutation found in the Caucasian population (10,14), and these studies were verified and extended to establish genotype-phenotype correlations in a cohort of patients from 11 countries (21).…”
mentioning
confidence: 99%
“…Our long-standing biochemical research into the mechanism of this critical flavoprotein (12) led us to explore the structure/ function relationships responsible for these phenotypes by expressing and purifying POR variants of interest reported in the literature (13)(14)(15)(16)(17)(18)(19)(20). The variant A287P was reported as the most common mutation found in the Caucasian population (10,14), and these studies were verified and extended to establish genotype-phenotype correlations in a cohort of patients from 11 countries (21).…”
mentioning
confidence: 99%
“…Thus, the contribution of common POR variants to variability of tacrolimus metabolism is of great interest. POR*28, the most common sequence variant in POR gene, induces an amino acid substitution (C>T, p.Ala503Val) and influence the electron binding moiety of POR [23] . A previous in vitro study showed that this mutation could decrease CYP3A4 activity.…”
Section: Discussionmentioning
confidence: 99%
“…P450 oxidoreductase complex operates as follows ( Figure 11): electrons from reduced NADPH (released as NADP+), are taken up by the FAD moiety, which is reduced to FADH 2 . Then FADH 2 reduces FMN to FMNH 2 , which in turn passes its two electrons to the CYP heme group, which is associated with the P450 oxidoreductase by electrostatic interactions (Huang et al, 2008). This electron transfer becomes a current of electron that P450 oxidoreductase must supply in the presence of high substrate concentrations.…”
Section: Redox Partners and Electron Transport Systemmentioning
confidence: 99%
“…Adapted from (Miller, W.L., 2005). Reprinted with permission from Huang et al, 2008. Copyright (2008 National Academy of Sciences, U.S.A. Figure 12) are electron transport hemeproteins which, similarly to cytochrome P450, are built around a central heme group.…”
Section: Redox Partners and Electron Transport Systemmentioning
confidence: 99%
See 1 more Smart Citation